Efektivitas Konseling Kelompok dengan Teknik Motivational Interviewing untuk Meningkatkan Motivasi Belajar Siswa Kelas IX SMP Negeri 19 Pontianak - Lili Arifiani; Muhammad Asrori; Amallia Putri (Edu Berkah Khatulistiwa, 2026)
Motivation is one of the most important factors that influences student learning achievement. In the learning process, motivation is considered as a driving force within students that generates learning activities and provides clear direction to learning activities so that desired goals can be achieved. Guidance and counseling teachers can also play a role in overcoming low student learning motivation, one of which is by providing group counseling services. This study aims to test the effectiveness of group counseling services with motivational interviewing techniques on increasing learning motivation of grade IX students at SMP Negeri 19 Pontianak. The method used is an experiment with a Pre-Experimental Design research design of the One-Group Pretest and Post-test Design. The research sample consisted of 6 students with the lowest learning motivation from a total population of 159 students in grades A-F. The calculation results show that the pre-test percentage is 65% with a low category, while the post-test reaches 87% with a medium category. The statistical test with Paired Sample T-test produced a T count of 17.249 and a sig value (2-tailed) of 0.000, which indicates that Ha is accepted and H0 is rejected, meaning that there is a significant difference between students' learning motivation before and after being given group counseling services with motivational interviewing techniques. Thus, it can be concluded that group counseling with motivational interviewing techniques is effective in increasing the learning motivation of class IX students of SMP Negeri 19 Pontianak.